Observational study to analyse the opioid titration process in the treatment of breakthrough pain of cancer patients in clinical practice - Lara Iglesias-Docampo; Paola Pimentel-Cáceres; Mª Paola García-Coves; José Luis Firvida-Pérez; Julio José Lambea-Sorrosal; Antonio Andrés Rueda-Ramos; Iker López-Calderero; Juan Antonio Núñez-Sobrino; Antonio Javier Jiménez-López; Ana Cabezón-Álvarez; Begoña Soler-López (Open Journal of Pain Medicine - Peertechz Publications, 2019)
Background: During the oncological disease, patients may suffer a special type of pain called breakthrough pain (BTP), defined as a transient exacerbation of pain that occurs either spontaneously, or in relation to a specific predictable or unpredictable trigger, despite relatively stable and adequately controlled background pain. Opioids are an essential part of BTP treatment, and its dosing adjustment should be performed irrespective of the basal dose of analgesia. However, in clinical practice it is unknown how opioids titration is completed. The context and purpose of the study: The objective of the study was to assess opioid titration process for the treatment of breakthrough pain (BTP) in cancer patients in usual clinical practice.  An observational study was completed in 17 Medical oncology departments. Information was collected on 165 cancer patients over 18 years of age, with controlled baseline pain and BTP, in whom an opioid was prescribed for BTP. The sequence of the titration process of the new opioid prescribed to the patient were recorded. Results: The mean age of the patients was 64.8 years (95% confidence interval: 63 to 66.5), and 69.1% were males (114). The active ingredients analysed were: Fentanyl (93% of patients), Morphine (4%), and Oxycodone (2%). Titration required: One step in 86.1% (142) of patients; two steps in 9.1% (15), three steps in 4.2% (7), and four steps in 0.6% (1). The mean time to next step in titration was 22.04 minutes (95% confidence interval: 17 to 27), with a median of 15 minutes; no significant differences were observed between the products administered. Conclusions: Most patients (86.1%) require only one step for opioid titration for BTP treatment. The conclusion is that titration of immediate-acting opioid in patients with BTP is a rapid process, adequate to the characteristics of the BTP, and is achieved at the doses recommended in the summaries of product characteristics.